Exploring augmentative and alternative communication in intensive care units: nurses' experiences, knowledge, and training preferences in Cyprus - Pampoulou, Eliada; Kyranou, Maria; Phylactou, Phivos; Papaioannou, Maria; Charalambous, Marina; Georgiou, Anastasios M.; Demetriou, Maria; Kyriakou, Neophytos; Lytra, Pani; Georgiou, Fotini; Palazis, Lakis (My University, 2025)
Nurses provide quality and safe care to critically ill patients in intensive care units (ICUs) who might also experience severe speech-language production and/or comprehension impairments. However, interpreting patients' communication efforts is not always possible for several reasons, such as lack of time or training. The current study aimed to investigate ICU nurses' Augmentative and Alternative Communication (AAC) knowledge and determine their preference for receiving training on AAC forms of communication.
Keywords: Augmentative and alternative communication (AAC); intensive care unit (ICU); knowledge; training; nurses